Contribution of the elevated thrombosis risk of males to the excess male mortality observed in COVID-19: an observational study. Issue 2 (25th February 2022) - Cohen, Kenneth Roy; Anderson, David; Ren, Sheng; Cook, David J
Abstract : Background: The mortality rate of COVID-19 is elevated in males compared with females. Objective: Determine the extent that the elevated thrombotic risk in males relative to females contributes to excess COVID-19 mortality in males. Design: Observational study. Setting: Data sourced from electronic medical records from over 200 US hospital systems. Participants: 60 877 patients aged 18 years and older hospitalised with COVID-19. Exposure: Exposure variable: biological sex; key variable of interest: thrombosis. Primary outcome measures: Primary outcome was COVID-19 mortality. We measured: (1) mortality rate of males relative to females, (2) rate of thrombotic diagnoses occurring during hospitalisation for COVID-19 in both sexes and (3) mortality rate when evidence of thrombosis was present. Results: The COVID-19 mortality rate of males was 29.9% higher than that of females. Males had a 35.8% higher rate of receiving a thrombotic diagnosis compared with females. The mortality rate of all patients with a thrombotic diagnosis was 40.0%—over twice that of patients with COVID-19 without a thrombotic diagnosis (adjusted OR 2.50 (2.37 to 2.64), p<0.001). When defining thrombosis as either a documented thrombotic diagnosis or a D-dimer level ≥3.0 µg/mL, 16.4% of the excess mortality in male patients could be explained by increased thrombotic risk. Conclusions: Our findings suggest the higher COVID-19 mortality rate in males may be significantly accounted for by the elevated risk of thrombosis among males. Understanding the mechanisms that underlie increased male thrombotic risk may allow for the advancement of effective anticoagulation strategies that reduce COVID-19 mortality in males.